'Quem não vive do mar, vive de quê?’ Sinalizadores de ‘repuxo’ do turismo em Torres/RS, a partir de ‘com-versações’ com moradores - Eme, Jennifer Bauer (My University, 2022)
The present dissertation has as a general objective to propose 'Repull' flags of Tourism in Torres/RS, from 'com-versations' with residents. It should be noted that repull is a maritime phenomenon that occurs from excess water that is pushed to the sand by the waves and, by gravity, returns to the sea, forming a channel also known as a return current. In the search, ahe reflexive metaphor 'Repull' of Tourism is associated with the discussion proposed by Baptista (2020), from Averse of Tourism, in recognition of the complex weave underlying the phenomenon. This is a production linked to Amorcomtur! - Group of Studies in Communication, Tourism, Loveliness and Autopoiesis (CNPq-UCS), linked to the Postgraduate Program in Tourism and Hospitality (PPGTURH) of the University of Caxias do Sul (UCS). The theoretical-conceptual paths of the research are transversalized by the vision: contemporary and complex, as understood by Morin (2005), Capra (1997, 2020), Crema (1989), Deleuze and Guattari (1995), and Santos (2003; 2019). The theoretical-conceptual trails referring to Tourism were made with authors like Moesch (2000, 2004), Moesch and Beni (2017), Gastal (2002, 2005a) and Baptista (2018, 2020b, 2021), in the understanding of Tourism-Weave-Ecosystem. Regarding narratives and 'com-versations', authors such as Medina (2006, 2014), Marcondes Filho (2008), Sodré (1986), Lima (2009, 2014), Maturana (1988) and Baptista (2018) stand out. In line with the epistemological orientation, the methodological strategy is the Cartography of Knowledge composed of the trail: Personal Knowledge, Theoretical Knowledge, Production Plant and Intuitive Dimension of Research, combined with the production of Rhizomatic Matrices, as a device for checking the fluent balance of the research (BAPTISTA, 2014, 2020b). From the production of the 'com-verse' and narratives of the residents, it was possible to propose five flags of the 'Repull' of Tourism, namely: 1) Ecosystem Planning for Tourism; 2) Culture of the interior as a tourist power of the place; 3) Constructions and (de)constructions of the architectural history of the place; 4) Ecosystem connections with the environment; and 5) Loving ties of place, locals and tourist. The flags are mainly marked by the ecosystem intertwining between them. It was noticed that, in Torres/RS, the main potentiality of Tourism's Blowdown is simplicity and the bonds of love, in everyday life, guided by the tranquility of the interior. In addition, the valuation of aspects such as safety, quality of life and the beautiful natural landscapes was recurrent in the residents' statements, as support for the strong affective bond of these subjects with Torres/RS. [resumo fornecido pelo autor]
A presente dissertação tem como objetivo geral propor sinalizadores de 'Repuxo' do Turismo em Torres/RS, a partir de 'com-versações' com moradores. Destaca-se que repuxo trata-se de um fenômeno marítimo que acontece a partir do excesso de água que é empurrado para a areia, pelas ondas e, que, pela gravidade, volta ao mar, formando um canal conhecido também como corrente de retorno. Na pesquisa, a metáfora reflexiva 'Repuxo' do Turismo está associada à discussão proposta por Baptista (2020), de Avesso do Turismo, como reconhecimento da trama complexa subjacente ao fenômeno. Trata-se de produção vinculada ao Amorcomtur! - Grupo de Estudos em Comunicação, Turismo, Amorosidade e Autopoiese (CNPq-UCS), ligado ao Programa de Pós-Graduação em Turismo e Hospitalidade (PPGTURH) da Universidade de Caxias do Sul (UCS). As trilhas teórico-conceituais da pesquisa são transversalizadas pela visão: contemporânea e complexa, conforme compreendida por Morin (2005), Capra (1997, 2020), Crema (1989), Deleuze e Guattari (1995), e Santos (2003; 2019). As trilhas teórico-conceituais referentes ao Turismo foram feitas com autores como Moesch (2000, 2004), Moesch e Beni (2017), Gastal (2002, 2005a) e Baptista (2018, 2020b, 2021), na compreensão de Turismo-Trama-Ecossistêmica. Em relação às narrativas e às 'com-versações', destacam-se autores como Medina (2006, 2014), Marcondes Filho (2008), Sodré (1986), Lima (2009, 2014), Maturana (1988) e Baptista (2018). Em alinhamento à orientação epistemológica, a estratégia metodológica é a Cartografia de Saberes composta pelas trilhas: Saberes Pessoais, Saberes Teóricos, Usina de Produção e Dimensão Intuitiva da Pesquisa, combinada com a produção das Matrizes Rizomáticas, como dispositivo de checagem do equilíbrio fluente da pesquisa (BAPTISTA, 2014, 2020b). A partir da produção das 'com-versações' e narrativas dos moradores, foi possível propor cinco sinalizadores de 'Repuxo' do Turismo, sendo eles: 1) Planejamento ecossistêmico do Turismo; 2) Cultura de interior como potência turística do lugar; 3) Construções e (des)construções da história arquitetônica do lugar; 4) Conexões ecossistêmicas com meio ambiente; e 5) Entrelaços de amorosidade de lugar, moradores e turistas. Os sinalizadores são marcados, principalmente, pelo entrelaçamento ecossistêmico entre eles. Percebeu-se que, em Torres/RS, o 'Repuxo' do Turismo tem como principal potencialidade a simplicidade e os laços de amorosidade, na vivência cotidiana, orientados pela tranquilidade do interior. Além disso, foi recorrente, nas falas dos moradores, a valorização de aspectos como segurança, qualidade de vida e as belas paisagens naturais, como sustentação para o forte laço afetivo desses sujeitos com Torres/RS. [resumo fornecido pelo autor]
Keywords: Turismo - Torres (RS); Moradores da cidade - Torres (RS) - Narrativas pessoais; Tourism - Torres (Brazil); City dwellers - Torres (Brazil) - Personal narratives